The international oil companies - Gordon, R; Sloan, L; Davis, G (Oxford Institute for Energy Studies, 2006)
Richard Gordon considers the prospects and challenges ahead; Chris Ross and Lane Sloan propose a navigation aid for energy leaders; Ged Davis looks at the future of IOCs.